2018
DOI: 10.3390/su10041216
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Exergy Analyses of Different Aluminum Reduction Technologies

Abstract: This paper examines and compares different aluminum reduction technologies found in the literature as alternatives to the current Hall-Heroult technology. The main inefficiencies in the current Hall-Heroult technology were identified and the advantages of the different proposed technologies over the Hall-Heroult technology were determined. The comparison between the different technologies, namely Hall-Heroult, wetted drained cathode, inert anode, and carbothermic, was based on energy and material requirements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…The generation 3 control system examined in this study is comparable with the intervals from Kermeli et al (2015) when using coal power in global production through the electrolysis process. Obaidat et al (2018) found that wettable cathodes, inert anodes and direct carbothermic reduction can save around 0.88, 1.4 and 0.62 tonnes CO 2 /tonne aluminium, respectively, compared with the GHG emissions prior to their respective implementation. The results in the "Results and analysis" section show that the wettable cathodes, inert anodes and direct carbothermic reduction can save 0.005-2.35, -0.11-2.05 and -0.37-4.98 tonnes CO 2 eq/tonne aluminium, respectively, which covers the values from Obaidat et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The generation 3 control system examined in this study is comparable with the intervals from Kermeli et al (2015) when using coal power in global production through the electrolysis process. Obaidat et al (2018) found that wettable cathodes, inert anodes and direct carbothermic reduction can save around 0.88, 1.4 and 0.62 tonnes CO 2 /tonne aluminium, respectively, compared with the GHG emissions prior to their respective implementation. The results in the "Results and analysis" section show that the wettable cathodes, inert anodes and direct carbothermic reduction can save 0.005-2.35, -0.11-2.05 and -0.37-4.98 tonnes CO 2 eq/tonne aluminium, respectively, which covers the values from Obaidat et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Obaidat et al (2018) found that wettable cathodes, inert anodes and direct carbothermic reduction can save around 0.88, 1.4 and 0.62 tonnes CO 2 /tonne aluminium, respectively, compared with the GHG emissions prior to their respective implementation. The results in the "Results and analysis" section show that the wettable cathodes, inert anodes and direct carbothermic reduction can save 0.005-2.35, -0.11-2.05 and -0.37-4.98 tonnes CO 2 eq/tonne aluminium, respectively, which covers the values from Obaidat et al (2018). Additionally, there is a consensus between our article and the article by Obaidat et al (2018) when examining the results for wind power in our article, which indicate that direct carbothermic reduction should provide the smallest GHG emission saving of the three measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In aluminum industry, Hall-Héroult electrolysis process is highly energy intensive [1]. For this purpose, considerable efforts are invested to optimize this process [2,3].…”
Section: Introductionmentioning
confidence: 99%